Firm-asymmetry and strategic outsourcing - Cao, Jiyun; Mukherjee, Arijit; Sinha, Uday Bhanu (Elsevier, 2017)
In contrast to the conventional wisdom, we show that a final goods producer may outsource input production to an outside supplier even if the final goods producer possesses a superior input-production technology compared to the outside supplier. Such an outsourcing may reduce consumer surplus and social welfare. We also show that, in the presence of outsourcing, innovation by the firm doing outsourcing to reduce the cost of in-house input production and to reduce the input coefficient in the final goods production may have significantly different implications for the consumers and the society.